Disparity in neonatal abstinence syndrome by race/ethnicity, socioeconomic status, and geography, in neonates ≥ 35 weeks gestational age. - Keith A Dookeran; Marina G Feffer; Kyla M Quigley; Phoebe E Troller; Chariya A Christmon; Janine Y Khan (PLoS ONE)
Neonatal abstinence syndrome (NAS) is associated with a range of adverse health outcomes, exorbitant health care costs, and race/ethnicity disparity. We examined key sociodemographic factors that may influence the national race/ethnicity disparity in the prevalence of NAS among Whites, Blacks and Hispanics. 2016 and 2019 cycles of cross-sectional data from HCUP-KID national all-payer pediatric inpatient-care database were used to estimate NAS prevalence (ICD-10CM code P96.1) in newborns ≥ 35 weeks gestational-age, excluding iatrogenic-cases (ICD-10CM code P96.2). Multivariable generalized-linear-models with predictive-margins were used to produce race/ethnicity-specific stratified-estimates for select sociodemographic factors, reported as risk-differences (RD) with 95% confidence-intervals (CI). Final models were adjusted for sex, payer-type, ecologic income-level, and hospital size, type, and region. The overall survey weighted-sample prevalence of NAS was 0.98% (i.e., 6282/638100) and did not differ over cycles. Blacks and Hispanics were significantly more likely than Whites to be in the lowest ecologic income quartile and on Medicaid. In fully-specified models, NAS prevalence among Whites was 1.45% (95% CI: 1.33, 1.57) higher than Blacks and 1.52% (95% CI: 1.39, 1.64) higher than Hispanics; and NAS among Blacks was 0.14% higher than Hispanics (95% CI: 0.03, 0.24). NAS prevalence was highest among Whites on Medicaid (RD: 3.79%; 95% CI: 3.55, 4.03) compared to Whites on private-insurance (RD: 0.33%; 95% CI: 0.27, 0.38), and Blacks (RD: 0.73%; 95% CI: 0.63, 0.83; RD: 0.15%; 95% CI: 0.08, 0.21), or Hispanics, with either payer-type (RD: 0.59%; 95% CI: 0.5, 0.67; RD: 0.09%; 95% CI: 0.03, 0.15) respectively. NAS prevalence was higher among Whites in the lowest income-quartile (RD: 2.22%; 95% CI: 1.99, 2.44) compared with Blacks (RD: 0.51%; 95% CI: 0.41, 0.61) and Hispanics (RD: 0.44%; 95% CI: 0.33, 0.54) in the same quartile, and all subgroups in other quartiles. NAS prevalence was higher among Whites in the Northeast (RD: 2.19%; 95% CI: 1.89, 2.5) compared to Blacks (RD: 0.54%; 95% CI: 0.33, 0.74) and Hispanics (RD: 0.31%; 95% CI: 0.17, 0.45). Although Blacks and Hispanics were more likely to be in the lowest income quartile and have Medicaid insurance, Whites on Medicaid, in the lowest income quartile, and in the Northeast, were found to have the highest NAS prevalence.